Microstructure and Mechanical Properties of Ni Matrix B4C Reinforced Functionally Graded Composites - Caligulu, Ugur; Durmus, Hulya; Akkas, Mehmet; Sahin, Baris (Int Inst Science Sintering (I I S S), 2021)
In this study, microstructure and mechanical properties of nickel matrix B4C reinforced functionally graded composites produced by powder metallurgy method were investigated. Samples with Ni+5% B4C, Ni +10% B4C, Ni+ 15% B4C and Ni+ 20% B4C compositions were sintered at 900 and 1050 degrees C for 60 minutes. Microhardness and wear tests along with optical microscopy, scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM-EDX) and X-ray diffraction (XRD) analyses were carried out to determine the mechanical properties, microstructure and phase composition of the samples. The results indicated that hardness and wear resistance increased with increases of B4C amount in nickel matrix.
Keywords: Ni; B4C; FGM; Microstructure; Mechanical Properties